Environmental management and its application in the Slovak Republic - Mariana Dubravská (Journal of Economic Development, Environment and People, 2013)
The Paper aims at implementation of environmnental management in the condition of Slovak Republic. Systems of the environmental management represent the mean of practical realization of environmental requirements, competitiveness indicator, tool of the sustainable development support and acknowledgement of good environmental behaviour by regulation of the business activities impacts. Standard scientific research methods included synthesis, analysis and comparative method.